Spatiotemporal delivery of multiple components of rhubarb-astragalus formula for the sysnergistic treatment of renal fibrosis - Zhang, Qibin; Ye, Xiaofeng; Zhu, Lin; Xu, Zhishi; Hou, Yu; Ke, Qiaoying; Feng, Jiawei; Xie, Xiaowei; Chen, Danfei; Piao, Ji-Gang; Wei, Yinghui (Frontiers in Pharmacology, 2024)
Purpose: Rhubarb (Rheum palmatum L.) and astragalus (Radix astragali) find widespread used in clinical formulations for treating chronic kidney disease (CKD). Notably, the key active components, total rhubarb anthraquinone (TRA) and total astragalus saponin (TAS), exhibit superiority over rhubarb and astragalus in terms of their clear composition, stability, quality control, small dosage, and efficacy for disease treatment. Additionally, astragalus polysaccharides (APS) significantly contribute to the treatment of renal fibrosis by modulating the gut microbiota. However, due to differences in the biopharmaceutical properties of these components, achieving synergistic effects remains challenging.This study aims to develop combined pellets (CPs) and evaluate the potential effect on unilateral ureteral obstruction (UUO)-induced renal fibrosis. Methods: The CPs pellets were obtained by combining TRA/TAS-loaded SNEDDS pellets and APS-loaded pellets, prepared using the fluidized bed coating process. The prepared pellets underwent evaluation for morphology, bulk density, hardness, and flowing property. Moreover, the in vitro release of the payloads was evaluated with the CHP Type I method. Furthermore, the unilateral ureteral obstruction (UUO) model was utilized to investigate the potential effects of CPs pellets on renal fibrosis and their contribution to gut microbiota modulation.The ex-vivo study demonstrated that the developed CPs pellets not only improved the dissolution of TRA and TAS but also delivered TRA/TAS and APS spatiotemporally to the appropriate site along the gastrointestinal tract. In an animal model of renal fibrosis (UUO rats), oral administration of the CPs ameliorated kidney histological pathology, reduced collagen deposition, and decreased the levels of inflammatory cytokines. The CPs also restored the disturbed gut microbiota induced by UUO surgery and protected the intestinal barrier.The developed CPs pellets represent a promising strategy for efficiently delivering active components in traditional Chinese medicine formulas, offering an effective approach for treating CKD.